(untitled) (Al-Academy, 2025)
In the current study (design variables and their reflection on quality attributes in industrial product design) the researcher tried to study the design variables that represent the change in different methods and treatments of design elements and explain their reflection on the quality attributes of industrial products. The current study consisted of presenting the problem of the study by explaining what is the concept of design variables. Its implications for the quality attributes of industrial products?